Management of Security Risk in the Energy Field - Gabriel Vasilescu; Passca Mihaela; Mihail Vătăsescu; Ciprian Jitea (The Global Environmental Engineers, 2014)
An integrated method for an efficient internal auditing of OHS applicable to the work systems met in hydrotechnical and hydroelectrical operations has been devised as part of the program NUCLEU/2010-2011 – Project PN 07 45 01 12. This project represents an approach in compliance with the European and national requirments aiming at increasing OHS level for companies involved in water construction works and also provides sustainability to the related environment.